Cultura ciudadana. Renegotiating the Boundary between State and Society - Stacey L. Hunt (Íconos)
In this paper I analyze the continued existence of the Colombian state despite widespread crime and violence. Contemporary theorists posit that the state must subscribe to the image of an entity that is relatively autonomous from civil society and able to monopolize violence. However, citizen culture (cultura ciudadana), the innovative crime reduction policy I study here, is based on the premise that the state is unable to provide security for its inhabitants given the existence of a culture of violence. The policy encourages citizens to assume responsibility for their own security provision by adopting a culture of citizenship. I argue that citizen culture functions to legitimize the state despite ongoing violence by transferring responsibility for security provision from the state to civil society. It does so by inundating public space with educational spectacles, symbols, and slogans that circumscribe public debate and instruct citizen’s behavior. Citizen culture uses educational and symbolic programming to shift responsibility for security provision from the state to society, thereby altering the boundary between state and society and redefining the very essence of the modern state.